Você está na página 1de 7

Copyiight Ren Baiiientos Page 1

THE LAPLACE TRANSFORMAND INITIAL VALUE PROBLEMS (Part I)


We are ready to apply the transform to initial value problems. The transform converts expressions involving
derivatives to algebraic ones involving the transform of the dependent variable because, as we learned earlier,
L{y
i
] = xL{y] - y(u) (1)
and
L{y''] = x
2
L{y] -xy(u) - y
i
(u) (2)
And by an inductive argument we also established the formula for higher derivatives:



Observe that the right hand side of this identity does not involve derivatives except for the initial conditions
y
(j)
(u) which are just real numbers. Hence, the Laplace transforms converts derivatives of an unknown
function into an algebraic equation in its transform.
It will be convenient to use the notation Y(s) in place of L{y]. The formula for the transform of y
i
then
becomes:
(3)

and similarly for the transform of higher derivatives:
L|y
(n)
| = x
n
Y(x) - x
n-1
y(u) -x
n-2
y'(u) - - y
(n-1)
(u)









Here is how the transform is used to solve initial value problems:

Let us solve a very simple equation to see how this works.
Example 1 Solve the IVP y
i
-y = u; y(u) = 2
Solution
y = kc
t
solves the differential equation and the initial condition requires that k = 2. Thus, the
solution is y = 2c
t
and this is something that we have seen several times before. Let us see what the
Laplace transform gives us:
o
n
(t)y
(n)
+o
n-1
(t)y
(n-1)
++o
1
(t)y
i
+ o
0
(t)y = (t)
y(t
0
) = y
0
, y
i
(t
0
) = y
1
, , y
(n-1)
(t
0
) = y
n-1

Given the initial value problem:
1) Apply the Laplace transform to both sides of the differential equation to obtain an algebraic equation in
(s).
2) Solve the algebraic equation for Y(s).
3) Find L
1
{Y(s)} to reproduce y(t).
L{y
i
] = xY(x) -y(u)
L|y
(n)
| = x
n
L{y] - x
n-1
y(u) -x
n-2
y'(u) - x
n-3
y''(u) -y
(n-1)
(u)
This side of the equation involves
derivatives of the unknown function y(t)
This side of the equation is an algebraic
equation in (s) = L{y(t)]
Copyiight Ren Baiiientos Page 2

Taking the transform of both sides of the differential equation:
L{y
i
- y] = L{u]
Applying linearity:
L{y
i
] -L{y] = u
Applying (S),
sY(s) -y(u) - Y(s) = u
where Y(s) = L{y]. Since y(u) = 2, after collecting like terms we have:
Y(s)(s -1) - 2 = u
Solving for (s):
(s) =
2
s - 1

Since Y(s) =L {y}, we can reproduce y(t) by taking the inverse transform of both sides:
y(t) = L
-1
_
2
s -1
_ = 2L
-1
_
1
s - 1
_
= 2e
t

as expected.
Clearly this is not a method that we would use for such a simple equation, but it works and it is specially
useful for situations in which the forcing function is piecewise defined or periodic.
Example 2 Solve the IVP 2y
i
+y = c
t
; y(u) = 1
Solution
This is a first order linear equation and may easily be solved with an integrating factor (the
integrating factor in this case isp = c
]
1
2
dt
). Let us see what the Laplace transform method gives us:
Taking the transform of both sides of the differential equation:
L{2y
i
+ y] = L{c
t
]
By linearity,
2L{y
i
] + L{y] = L{c
t
]
Applying (3),
2(s(s) -y(u)) +(s) =
1
s - 1

Solving for (s)
2s(s) - 2 + (s) =
1
s -1

(2s + 1)(s) =
1
s - 1
+ 2
Hence,
(s) =
1
(s -1)(2s + 1)
+
2
2s +1

Decomposing the first term into partial fractions,
1
(s -1)(2s +1)
=
1S
s - 1
-
2S
2s + 1

Thus,
(s) =
1S
s - 1
-
2S
2s +1
+
2
2s +1

(s) =
1S
s -1
+
4S
2s +1

We are ready for L
-1
:
Copyiight Ren Baiiientos Page S

y(t) =
1
S
L
-1
_
1
s - 1
_ +
4
S
L
-1
_
1
2s +1
_
=
1
S
L
-1
_
1
s - 1
_ +
4
S
L
-1
_
1
2(s +12)
_
=
1
S
L
-1
_
1
s - 1
_ +
2
S
L
-1
_
1
(s -(-12))
_
=
1
3
e
t
+
2
3
e
-
1
2
t

Example 3 [a second order equation] Solve the IVP y
ii
+ y = 1; y(u) = u, y
i
(u) = -2
Solution
Once again, taking the Laplace transform of both sides, we obtain:
L{y
ii
+ y] = L{1]
or
L{y
ii
] + L{y] =
1
s

s
2
Y(s) - sy(u) - y
i
(u) + Y(s) =
1
s



Substituting the initial conditionsy(u) = u, y
i
(u) = -2,
s
2
Y(s) - s u -(-2) + Y(s) =
1
s

Simplifying and collecting (s):
(s
2
+ 1)(s) + 2 =
1
s

Solving for (s):
(s) =
1
s(s
2
+ 1)
-
2
(s
2
+ 1)

Thus,
y(t) = L
-1
{(s)] = L
-1
_
1
s(s
2
+1)
-
2
(s
2
+1)
_
It is now a matter of computing this inverse transform. The first term requires partial fractions and
the second is clearly identifiable with the sine function. Verify that
1
s(s
2
+1)
=
1
s
-
s
s
2
+ 1

Thus,
y(t) = L
-1
_
1
s(s
2
+ 1)
-
2
(s
2
+1)
_
= L
-1
_
1
s
-
s
s
2
+ 1
_ - 2L
-1
_
1
(s
2
+ 1)
_
= 1 -us t -2stnt
Example 4 [a typical spring-mass system] Solve the IVP x
ii
+x = 8cos St ; x(u) = 1, x
i
(u) = u
Solution
Taking the Laplace transform of both sides, we obtain:
L{x
ii
+x] = 8L{cos St]
or
L{y
ii
] L{y]
Copyiight Ren Baiiientos Page 4

s
2
X(s) -s x(u) - x
i
(u) +X(s) =
8s
s
2
+ 9



Substituting the initial conditions x(u) = 1, x
i
(u) = u,
s
2
X(s) -s 1 -u + X(s) =
8s
s
2
+ 9

Simplifying and collectingX(s):
(s
2
+1)X(s) -s =
8s
s
2
+ 9

Solving for X(s):
X(s) =
8s
(s
2
+ 1)(s
2
+9)
+
s
(s
2
+ 1)

Thus,
x(t) = L
-1
{X(s)] = L
-1
_
8s
(s
2
+ 1)(s
2
+9)
+
s
(s
2
+1)
_
Verify that
8s
(s
2
+ 1)(s
2
+9)
=
s
s
2
+ 1
-
s
s
2
+ 9

Thus,
x(t) = L
-1
]
s
s
2
+1
-
s
s
2
+9
+
s
s
2
+ 1

= L
-1
_
2s
s
2
+ 1
-
s
s
2
+9
_
= 2us t - us 3t
Example 5 [over-damped spring-mass system] Solve the IVP Sx
ii
+ 4x
i
+ x = u; x(u) = u, x
i
(u) = -2
Solution
Taking the Laplace transform of both sides, we obtain:
L{Sx
ii
+ 4x
i
+ x] = L{u]
Thus,
S(s
2
X(s) -s x(u) - x
i
(u)) + 4(s X(s) -x(u)) +X(s) = u
Substituting the initial conditions,
Ss
2
X(s) +6 +4sX(s) +X(s) = u
X(s)|Ss
2
+4s +1] = -6
Hence,
X(s) = -
6
Ss
2
+4s + 1
=
-6
(Ss + 1)(s +1)

By partial fractions,
X(s) =
S
s +1
-
9
Ss + 1

Applying the inverse transform,
x(t) = SL
-1
_
1
s + 1
_ -
9
S
L
-1
_
1
s + 1S
_
we obtain the typical solution associated with of over-damped systems:
x(t) = -3e
-t3
+3e
-t

Example 6 [critically damped system] Solve the IVP y
ii
+ 4y
i
+ 4y = u; y(u) = 4, y'(u) = u.

L{x
ii
] L{x]
Copyiight Ren Baiiientos Page S

Solution
Taking the Laplace transform of both sides, we obtain:
L{y
ii
+ 4y
i
+4y] = u
or
(s
2
Y(s) - s y(u) - y'(u)) +4(sY(s) -y(u)) + 4Y(s) = u
Substituting the initial conditions,
|s
2
Y(s) - 4s] +4|sY(s) -4] +4Y(s) = u
Solving for (s):
(s)|s
2
+ 4s +4] = 4s +16
or
(s) =
4s +16
s
2
+ 4s +4

=
4s
(s +2)
2
+
16
(s + 2)
2

We recognize the second term on the right hand side of this equation to be of the form 1s
2
with the shift
s - s + 2 so we expect to use the First Shifting Theorem at some point. The first term needs to be treated
with partial fractions:
4s
(s + 2)
2
=
A
s + 2
+
B
(s + 2)
2
= A = 4 anu B = -8
Thus,
(s) =
4
s +2
+
-8
(s +2)
2
+
16
(s + 2)
2

=
4
s + 2
+
8
(s + 2)
2

Therefore,
y(t) = L
-1
_
4
s +2
+
8
(s +2)
2
_
= 4L
-1
_
1
s +2
_ + 8L
-1
_
1
(s + 2)
2
_


y(t) = 4c
-2t
+8tc
-2t

This is a typical solution of critically damped systems.
Example 7 [resonant system] Solve the IVP 2x
ii
+ S2x = Ssin4t ; x(u) = u, x
i
(u) = u
Solution
Taking the Laplace transform of both sides, we obtain:
L{2x
ii
+ S2x] = SL{sin4t]
Thus,
2(s
2
X(s) -s x(u) - x
i
(u)) +S2X(s) =
2u
s
2
+ 16

Substituting the initial conditions,
2s
2
X(s) +S2X(s) =
2u
s
2
+ 16

X(s)|s
2
+16] =
1u
s
2
+16

First shifting Theorem
with 1s
2

Copyiight Ren Baiiientos Page 6

Hence,
X(s) =
1u
(s
2
+ 16)
2

In order to findx(t), we inverse transform:
x(t) = L
-1
_
1u
(s
2
+ 16)
2
_
However, a quick glance to a basic table of transforms reveals that there is no entry that can help us
to find this inverse transform. However, a more extensive table has an entry that states:
L{sinkt -kt cos kt] =
2k
3
(s
2
+ k
2
)
2

Using this formula in the reverse direction with k = 4,
x(t) = L
-1
_
1u
(s
2
+ 16)
2
_ =
1u
128
L
-1
_
128
(s
2
+ 4
2
)
2
_
=
5
4
(stn4t - 4t us kt)
This example illustrates a fairly common problem that arises in the study of the transform: how do we find the
inverse transform of the product of two functions F(s) and0(s)? That is, how do we findL
-1
{F(s)0(s)]?
The answer to this question comes in the form of the convolution Theorem, which states:
L
-1
{F(s)0(s)] = _ ()
t
0
g(t - )J
where (t) = L
-1
{F(s)] and g(t) = L
-1
{0(s)]. The integral operation is called the convolution of the
functions and g, denoted by ( - g)(t):
( - g)(t) = _ ()
t
0
g(t - )J
In the previous example, we may use the convolution theorem to obtainx(t) by realizing that
1
(s
2
+4
2
)
2
=
1
(s
2
+4
2
)

1
(s
2
+4
2
)
and identifying the functions F(s) = 1(s
2
+ 16) and0(s) = 1(s
2
+ 16). Thus,
x(t) = L
-1
_
1u
(s
2
+16)
2
_ = 1uL
-1
_
1
s
2
+ 16

1
s
2
+ 16
_
= 1u _
1
4
sin4
1
4
t
0
sin((4(t -)) J
=
1u
16
_ sin4
t
0
sin(4(t - )) J
Exercise: Evaluate the integral and obtain x(t).
Example 8[piecewise defined forcing functions] Solve the IVP 0
ii
- 490 = 98 ]
u u t < S
1 t S
; 0(u) = 2,
0
i
(u) = u.
Solution
Using the unit step function, we may write the forcing functions as(t) = 98u(t -S). Hence the
equation can be written as
0
ii
-490 = 98u(t -S)
Taking the Laplace transform of both sides, we obtain:
L{0
ii
- 490] = 98L{u(t - S)]
Thus,
Copyiight Ren Baiiientos Page 7

s
2
(s) -s 0(u) - 0
i
(u) - 49(s) = 98
c
-5s
s

Substituting the initial conditions:
s
2
(s) - 2s - 49(s) = 98
c
-5s
s

Solving for (s):
(s) =
98c
-5s
s(s
2
- 49)
+
2s
(s
2
-49)

The first term needs to be decomposed by partial fractions. The second term may be identified with
the transform of a hyperbolic cosine:
98
s(s
2
-49)
=
-2
s
+
1
(s + 7)
+
1
s - 7

Hence,
(s) = _
1
(s + 7)
+
1
s - 7
-
2
s
] c
-5s
+
2s
(s
2
- 49)

To obtain 0(t) we use the inverse transform:
0(t) = L
-1
__
1
(s + 7)
+
1
s - 7
-
2
s
] c
-5s
+
2s
(s
2
-49)
_
= u(t - S) (c
-7t
+ c
7t
- 2)|
t-5
+2cosh7t
= |c
-7(t-5)
+ c
7(t-5)
-2] u(t - S) + 2cosh7t
The effect of the forcing function in the previous example can be more appreciated if we write the solution
without the unit step function:
If t < S,
0(t) = 2cosh7t
If t S,
0(t) = |c
-7(t-5)
+c
7(t-5)
- 2] + 2cosh7t
= c
-7(t-5)
+c
7(t-5)
+ c
-7t
+ c
7t
- 2
= 2cosh(7t - SS) +2cosh7t -2
Hence,
0(t) = _
2cosh7t i t < S
2|cosh(7t -SS) +cosh7t] - 2 i t S



0(t) is continuous at the interface t = S: 2coshSS = 2|cosh(u) + coshSS] -2 = 1.S8 1u
15
.
2 4 6 8 10
210
24
410
24
610
24
810
24